2018
DOI: 10.18037/ausbd.552716
|View full text |Cite
|
Sign up to set email alerts
|

Farklı Yaş Gruplarındaki (Kuşaklardaki) Çalışanların İşyerinde Eğlenmeye Yönelik Tutumu, İşyerinde Eğlenme Düzeyi, İş Tatmini ve İşten Ayrılma Niyetine İlişkin Bir Araştırma

Abstract: This paper aims to present attitudes towards fun at work, experienced fun, job satisfaction and turnover intention of age generations; determine relations between attitudes towards entertainment at work, experienced fun, job satisfaction, and turnover intention. Also, another purpose of this research is to find differences between attitudes towards entertainment at work, experienced fun, job satisfaction, and turnover intention in terms of generations. Research was carried out at a manufacturing factory. Resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…While the post WW2 generation and the boomers valued work as a central aspect of their lives, the millenials display more individualistic traits than the previous generations and they value work-life balance and leisure time (Foster 2013;Twenge 2010). A study on white collar workers in Turkey also demonstrated that attitudes towards entertainment at work have direct effect on turnover intension and that particularly members of Generation Y value having fun and interpersonal relations at work (Pekdemir et. al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…While the post WW2 generation and the boomers valued work as a central aspect of their lives, the millenials display more individualistic traits than the previous generations and they value work-life balance and leisure time (Foster 2013;Twenge 2010). A study on white collar workers in Turkey also demonstrated that attitudes towards entertainment at work have direct effect on turnover intension and that particularly members of Generation Y value having fun and interpersonal relations at work (Pekdemir et. al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Though workplace fun has been investigated as the predictor of various work-related outcomes research relating fun to life satisfaction is scant. Also, workplace fun investigations often neglect the humane influence as individuals from different generations tend to differ in their thinking and behaviour (Pekdemir et al, 2018). In recent years, organizations have increasingly faced the challenge to create the same work environment for people with different age groups, thought processes, personalities and behaviours.…”
Section: Introductionmentioning
confidence: 99%